Differences in hamstring activation characteristics between the acceleration and maximum-speed phases of sprinting - Higashihara, A.; Nagano, Y.; Ono, T.; Fukubayashi, T. (Journal of Sports Sciences, 2018)
This study aimed to investigate activation characteristics of the biceps femoris long head (BFlh) and semitendinosus (ST) muscles during the acceleration and maximum-speed phases of sprinting. Lower-extremity kinematics and electromyographic (EMG) activities of the BFlh and ST muscles were examined during the acceleration sprint and maximum-speed sprint in 13 male sprinters during an overground sprinting. Differences in hamstring activation during each divided phases and in the hip and knee joint angles and torques at each time point of the sprinting gait cycle were determined between two sprints. During the early stance of the acceleration sprint, the hip extension torque was significantly greater than during the maximum-speed sprint, and the relative EMG activation of the BFlh muscle was significantly higher than that of the ST muscle. During the late stance and terminal mid-swing of maximum-speed sprint, the knee was more extended and a higher knee flexion moment was observed compared to the acceleration sprint, and the ST muscle showed higher activation than that of the BFlh. These results indicate that the functional demands of the medial and lateral hamstring muscles differ between two different sprint performances.